Increasing motivation through dynamic presentation skills - Arnold, Craig; Winberry, Kathy (California : Lee Canter & Associates, 1995)
In the first section of the video, presenter will present strategies for incorporating an attention-grabbing anticipatory set into every lessons. In the secong section, presenter touch on effective communication skills
Executive producer, Lee Canter
Narrator: Ron Snow
Host: Lee Canter
Keywords: Public speaking; Oral communication; Motivation in education